Authorship in the culture industry:|Azra Kohen’s series of novels Fi, Çi, and Pi - Varol, Cansu. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
This study is an attempt to place the contemporary author somewhere between literature and the media culture of our day. On the best-seller shelves since 2014 when it was first published, Azra Kohen’s trilogy Fi, Çi, Pi has been frequently subjected to discussions in Turkish literature. As a result, the writer has become a popular figure who has been invited to television shows, universities, newspaper interviews since then. The story narrated in the trilogy also promised such rating for a production company that three years after its first publication, it was adapted to screen as internet series. This master thesis analyses Kohen’s contradictory attitude as a writer regarding the appearances in media and the series adaptation: while claiming that her only concern is to change the world, the writer comments on her authorship as frequently as possible. This ambivalent perception of (non) authorship is analysed in the light of literary, cultural and critical theories applied to the trilogy and the appearances in the media. In addition to a glance at the characters, the issues of corruption, fame and beneficial relationships in business and media platforms are comparatively analysed both in the trilogy and its screen adaptation. The reasons of the changes in the process of adaptation are discussed in the light of cultural theory. The result of this study shows that Kohen’s idealistic intentions are challenged by capitalistic motives throughout the process.
Keywords: Cultural industries.